Charge boosting and storage by tailoring rhombus all-inorganic perovskite nanoarrays for robust triboelectric nanogenerators. (August 2020) - Du, Jian; Duan, Jialong; Yang, Xiya; Wang, Yudi; Duan, Yanyan; Tang, Qunwei
Abstract: Triboelectric nanogenerator (TENG) is an advanced energy conversion device to harvest low-frequent mechanical energy from nature, and boosting triboelectric charge density and regulating charge storage behavior are promising solutions to improve their output performances. In this work, rhombus Co(OH)(CO3 )0.5 /Pt/CsPbIBr2 multilayer nanoarray is tailored as a friction layer coupled with poly(vinylidene fluoride) to increase the in-depth distribution of triboelectric charges and to block the combination with induced positive charges on the electrode, the champion perovskite TENG achieves a short-circuit current density of 3.1 μA cm −2, an open-circuit voltage of 243 V and a triboelectric charge density of 9.57 nC cm −2, which can instantaneously light up 61 commercial LEDs at per contact. Due to the reduced charge loss in metallic electrode and increased internal-space-charge zones of triboelectric charges in frictional layer assisted by the bottom Co(OH)(CO3 )0.5 and intercalated Pt layers, the tri-layered Co(OH)(CO3 )0.5 /Pt/CsPbIBr2 raises the power density peak by a factor of 4.5, reaching 2.04 W m −2 at a contact frequency of 0.5 Hz. In addition, the perovskite TENGs demonstrate an excellent stability over 1350 cycles test in ambient atmosphere. This work may provide new insights on manufacturing semiconductor-featured TENG platforms. Graphical abstract: Image 1 Highlights: Rhombus Co(OH)(CO3 )0.5 /Pt/CsPbIBr2 nanoarray is made as a friction layer for perovskite TENGs. The impacts of preparation conditions on the output performances are systematically studied. The champion perovskite TENG achieves an Isc of 3.1 μA cm −2, a Voc of 243 V and a Qsc of 9.57 nC cm −2 . The peak power density is increased by 4.5 times in comparison to pristine device.